IgG4-related pleural effusion with high adenosine deaminase levels: A case report and literature review. Issue 11 (19th March 2021) - Shimoda, Masafumi; Tanaka, Yoshiaki; Morimoto, Kozo; Okumura, Masao; Shimoda, Kiyomi; Takemura, Tamiko; Oka, Teruaki; Yoshiyama, Takashi; Yoshimori, Kozo; Ohta, Ken
Abstract: Rationale: Levels of pleural fluid adenosine deaminase (ADA), a useful marker for the diagnosis of tuberculous pleurisy, are elevated in some reports of immunoglobulin G4 (IgG4)-related pleural effusion. We describe a patient with IgG4-related pleural effusion who exhibited a high concentration of ADA. Furthermore, we reviewed the literature to compare patients with IgG4-related pleural effusion and tuberculous pleurisy. Patient concerns: A 75-year-old male patient had dyspnea for 1 month with a left pleural effusion that was exudative, lymphocyte dominant. The pleural fluid test results revealed a total protein (TP) concentration of 6.60 g/dl, a lactate dehydrogenase (LDH) level of 383 IU/dl, and an ADA concentration of 54.5 U/L. An interferon gamma release assay showed a negative result. Diagnoses: Histological analysis of the thoracoscopic pleural biopsy revealed lymphoplasmacytic infiltration, with 80 IgG4-positive plasma cells/high-power field, and an IgG4/IgG ratio of approximately 40% to 50%. Other diseases were ruled out based on symptoms, negative autoimmune antigen results, and histopathologic findings. Thus, he was diagnosed with IgG4-related pleural effusion. Interventions: He received 15 mg of prednisolone as therapy. Outcomes: His pleural effusion and symptoms improved gradually within several months, and prednisolone was tapered to 6 mg daily. Lessons: It is important to distinguish between IgG4-related pleural effusion and tuberculous pleurisy. Therefore, we compared 22 patients with IgG4-related pleural effusion from PubMed and the Japan Medical Abstracts Society to 40 patients with tuberculous pleurisy at Fukujuji Hospital from January 2017 to May 2019. According to thoracentesis findings, 14 of 18 patients with IgG4-related pleural effusion had high ADA more than 40 U/L. The pleural effusion of patients with IgG4-related pleural effusion showed higher TP levels ( P  < .001) and lower LDH ( P  < .001) and ADA levels ( P = .002) than those with tuberculous pleurisy. Moreover, the pleural fluid ADA/TP ratio was a good predictor for differentiating IgG4-related pleural effusion and tuberculous pleurisy (area under the receiver operating characteristic curve of 0.909; 95% confidence level: 0.824–0.994). Abstract : Supplemental Digital Content is available in the text